Influence of key parametres of bridge crane’s mechanisms on its productivity - N. S. Galdin; O. V. Kurbatskaya; S. V. Eremina (Вестник СибАДИ, 2017)
Productivity of bridge cranes depends on performance of mechanisms of moving and lifting loads of bridge cranes. The article contains data on influencing speeds of crane’s movement, cargo cart, speed of loads lifting, and also ways of crane’s movement, cargo cart, height of lifting load and other factors on its productivity. There are presented functional dependences of bridge cranes’ productivity on influencing factors.